Konsolidasi Hegemoni Neoliberal melalui Agenda Global Governance Wef Pasca Krisis 2008 - Alindha Cahyani (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This paper analyzes the role of the World Economic Forum (WEF) in shaping global governance after the 2008 financial crisis using a non-state-centric global governance perspective. It examines how the WEF, through various agendas such as the Global Redesign Initiative, Fourth Industrial Revolution, and The Great Reset, positions itself as a key actor in formulating responses to global instability. Despite promoting a narrative of collaboration, inclusivity, and multi-stakeholder partnerships, the analysis shows that the WEF actually refines and reproduces neoliberal hegemony through the dominance of private actors, market-based approaches, and undemocratic normative authority. This study also finds that the global governance mechanisms promoted by the WEF tend to widen inequality, create symbolic participation, and reinforce the power of the global economic elite. These findings highlight the normative dilemma in contemporary global governance and the need for a more accountable, inclusive, and public interest-oriented governance model.